2022
DOI: 10.1111/ijfs.16118
|View full text |Cite
|
Sign up to set email alerts
|

Structural, antioxidant, antibacterial and biodegradation properties of rice straw xylan (native and modified) based biofilms

Abstract: Summary The present study involved valorisation of rice straw by conversion of its constituent polymer xylan and chemically modified xylans into biofilms. Hemicellulosic xylan (19.94%) extracted with 10% NaOH (85 °C, 2.6 h) was chemically modified to acetylated (AX) and carboxymethylated xylan (CMX). Biofilms were prepared by reaction of xylan/modified xylan (1% and 2%) with polyvinyl alcohol using eco‐friendly and cheap cross‐linker citric acid and glycerol as plasticiser. 2% xylan biofilms showed maximum inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 32 publications
0
0
0
Order By: Relevance
“…The study results indicated that the addition of CA not only acted as a plasticizer but also improved the flexibility and processability of the material by forming ester bonds with the hemicellulose chains. Kapil et al [ 95 ] chemically modified rice straw xylan into acetylated xylan (AX) and carboxymethylated xylan (CMX) and created bio-composite films with polyvinyl alcohol (PVA) and CA. The introduction of AX and CMX enhanced the mechanical strength of the bio-composite films.…”
Section: Applications Of Gobp Hemicellulosementioning
confidence: 99%
See 2 more Smart Citations
“…The study results indicated that the addition of CA not only acted as a plasticizer but also improved the flexibility and processability of the material by forming ester bonds with the hemicellulose chains. Kapil et al [ 95 ] chemically modified rice straw xylan into acetylated xylan (AX) and carboxymethylated xylan (CMX) and created bio-composite films with polyvinyl alcohol (PVA) and CA. The introduction of AX and CMX enhanced the mechanical strength of the bio-composite films.…”
Section: Applications Of Gobp Hemicellulosementioning
confidence: 99%
“…However, high concentrations of AX and CMX could lead to uneven intermolecular cross-linking, reducing the elongation at break of the films. The acetylation process reduced the number of free hydroxyl groups, thereby decreasing the antioxidant activity [ 95 ]. This suggests the need to prepare different modified hemicellulose-based materials according to specific requirements.…”
Section: Applications Of Gobp Hemicellulosementioning
confidence: 99%
See 1 more Smart Citation